Is health promotion in sports clubs associated with adolescent participants' fruit and vegetable consumption? - Heikkilä L; Korpelainen R; Aira T; Alanko L; Heinonen OJ; Kokko S; Parkkari J; Savonen K; Toivo K; Valtonen M; Vasankari T; Villberg J; et al. (OXFORD UNIV PRESS, 2025)
Background: Although sports clubs' potential for health promotion is acknowledged, research on whether they promote healthy eating is limited. We aimed to evaluate Finnish youth sports clubs' health promotion orientation, as well as associations between sports clubs' health promotion orientation, coaches' nutritional discussions and sports club participants' (SPs') fruit and/or vegetable consumption.
Methods: The cross-sectional study included 554 SPs aged 14-16 years, 275 club officials and 311 coaches. Participants replied to questionnaires about sports clubs' health promotion and their own health behaviours, including dietary habits. Health promotion orientation was estimated using a Health Promoting Sports Club (HPSC) index (range 0-22) and nutritional discussions and fruit and/or vegetable consumption as frequencies. A mixed-effects multivariable logistic regression was used to analyse the associations.
Results: Most sports clubs (69%) had a high health promotion orientation, but the variation between the clubs was wide (HPSC index range 5-21). SPs' daily fruit and/or vegetable consumption was associated with female gender [odds ratio (OR) 3.48, 95% confidence interval (CI) 2.23-5.42, P < 0.001], better self-rated health (OR 3.26, 95% CI 1.13-9.41, P = 0.03), higher average school grades (OR 1.67, 95% CI 1.04-2.67, P = 0.03), and SPs' responses that their coach had often discussed nutrition (OR 2.11, 95% CI 1.41-3.14, P < 0.001).
Conclusion: Although sports clubs' orientation towards health promotion was mostly high, it seems not to be enough to promote healthy eating among adolescent participants. Instead, coaches' nutritional discussions were associated with adolescents' fruit and/or vegetable consumption.